EFL STUDENTS' ONLINE LEARNING: EPISTEMIC BELIEFS DETERMINE LEARNING STRATEGIES - Ismarita Ida Rahmiati; Ive Emaliana (EDUCAFL : Journal of Education of English as Foreign Language, 2019)
This study aimed to examine EFL students' cognitive processing, notably based on their epistemic beliefs views and learning strategies towards self-directed online learning. A descriptive quantitative method was used to explore 100 students' learning strategies. The focus is on examining individual knowledge construction through active cognitive engagement on English language exposures and aquisition in online community. The results suggest that students with more sophisticated epistemic beliefs have different learning strategies compare to those who posses simple ones. Students' characteristics which appear to impact their use of learning strategies are discussed. Suggestions for instructional strategies are offered.